2018
DOI: 10.1016/j.omtn.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Oligonucleotides against miR-21 Inhibit the Growth and Metastasis of Colorectal Carcinoma via the DUSP8 Pathway

Abstract: Accumulating research has documented that microRNA-21 (miR-21) plays an important role in the development of human colorectal carcinoma (CRC). Our recent work also showed that antisense oligonucleotides (ASOs) against miR-21 can impair the growth of CRC cells in vitro. However, the potential role of miR-21 in gene therapy against CRC remains to be fully elucidated. Here, we further observed the effect of ASOs against miR-21 on the growth and metastasis of CRC in vivo using a xenograft model of human CRC. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 53 publications
(62 reference statements)
2
20
0
Order By: Relevance
“…It is well established that miRNAs are involved in tumorigenesis by modulating the expression of their target genes (7). Preceding studies revealed that miR-21 functions as a tumor suppressor or an oncogene in gastric carcinoma (21), colorectal carcinoma (22), hepatocellular carcinoma (23) and acute myeloid leukemias (13). In the present study, it was demonstrated that miR-21 was significantly upregulated and KLF5 was significantly downregulated in AML cells, compared with normal bone marrow cells.…”
Section: Discussionsupporting
confidence: 50%
“…It is well established that miRNAs are involved in tumorigenesis by modulating the expression of their target genes (7). Preceding studies revealed that miR-21 functions as a tumor suppressor or an oncogene in gastric carcinoma (21), colorectal carcinoma (22), hepatocellular carcinoma (23) and acute myeloid leukemias (13). In the present study, it was demonstrated that miR-21 was significantly upregulated and KLF5 was significantly downregulated in AML cells, compared with normal bone marrow cells.…”
Section: Discussionsupporting
confidence: 50%
“…ILK negatively regulates the expression of DUSP8 [39], a MAPK phosphatase upregulated in our study, and DUSP8 dephosphorylates and inactivates JNK [40,41]. Inhibition of ILK/AKT decreases miR-21 in vestibular schwannoma and meningioma cells [42], and targeting miR-21 with antisense oligonucleotides (ASOs) inhibits growth and metastasis via upregulation of DUSP8 in colorectal carcinoma [43]. MARVELD3, a transmembrane protein of tight junctions [44,45] upregulated in our study, inhibits JNK activity via recruitment of MEKK1 to cell junctions [46].…”
Section: Discussionmentioning
confidence: 90%
“…For instance, Wei et al reported that MALAT1-shRNA treatment alleviated the in ammatory injury after lung transplant ischemia-reperfusion by downregulating IL-8 and inhibiting in ltration and activation of neutrophils [47]. Similarly, our previous work also showed that ASOs against miR-21 could reduce the growth and metastasis of human CRC cells in vivo and in vitro [48]. To evaluate the potential value of MAPK4 targeting in ALI treatment, herein, we assessed the possible effects of MAPK4-shRNA pre-treatment on the pathology of ALI.…”
Section: Discussionmentioning
confidence: 70%